Percutaneous endopyelotomy in the treatment of ureteropelvic junction obstruction - Lojanapiwat B. (2014)
Introduction: Current advances in endourology, percutaneous endopyelotomy has now become the preferred treatment for ureteropelvic junction obstruction. Many advantages of endopyelotomy compared to open correction are decreasing postoperative pain, shorter operative time and short recovery time. Patients and Method: Percutaneous endopyelotomy was performed in 15 patients. Nine patients had previous open kidney and upper ureteral surgery. 11 patients had associated renal calculi. The incised ureteropehic junction was stented with an endopyelotomy stent size 14/7. The stent was removed 6 weeks postoperatively. Results: 14 patients (93%) remain symptom-free and 11 (73%) had improvement of their symptoms and postoperative intravenous pyelogram or renogram after follow up at 12-38 months (over 18 months). Conclusion: Percutaneous endopyelotomy is widely accepted as the first choice for correction of ureteropelvic junction obstruction due to less morbidity and with a high success rate.